STUDI TENTANG NILAI KAPASITAS OKSIGEN MAKSIMAL (VO2 MAKS) PADA KOMUNITAS SENAM ZUMBA DI SANGGAR SENAM SAYA SUKA KAMU (SSK) KOTA MALANG TAHUN 2017 - Krisdayanti P, Carinada Oki; Raharjo, Slamet; Saichudin, Saichudin (Jurnal Sport Science, 2017)
Abstract :Zumba dance is one of the most popular aerobic sports in Indonesia. The aim of this reasearch is, to determine the value of VO2 Max which owned by the mambers zumba dance in gymnastics (SSK) community of Malang city 2017. This research uses quantitative descriptive approach, data collecting technique by using Queens College Step Test is a test to determine the value of maximal oxygen capacity (VO2 max) by doing up and down movement of the bench for 3 minutes and using the questionnaire as supporting information. The results of research, variable of age and sex dominant interrelatedness towards the value of VO2 max, according to both collation of the higest and lowest value of VO2 max with other components. While the hospital sheet variable has the lowest interrelatedness toward the subject value of VO2 max. Conclusion from the research result shows that the average value of VO2 max mamber of zumba dance in gymnastics (SSK) OfÂ Malang city 2017 is fair.Keywords :Maximum Oxygen Volume (VO2 Max), Fitness, Durability, Surveys, Gymnastics Saya Suka Kamu (SSK).